Examination of self-respect and decision-making styles in decisionmaking of individuals participating in the training of camp leadership - Gacar, Atalay; Nacar, Eyyup; Coşkuner, Zeki; Yalçın, İlimdar (My University, 2013)
The decision; means selecting the most appropriate one from various possible forms of action that will be able to possible according to available opportunities and conditions in order to achieve a goal. Also decision-making is the whole of cognitive and behavioral efforts related to make a choice and selection in the face of the various situations and events. 108 volunteer leader candidates were participated in our study, by reaching 86.4% of 125 people participating in the Training of Camp Learship organized in Kapizli April 23 Scouting and Camp Training Center in Silifke District of Mersin between 28 January and 2 February 2013.In our study, it was aimed to examine the self-respect and decision-making styles in decision-making of individuals participating in the Training of Camp Learship in terms of some variables. To achieve this goal, it was determined, by using "Melbourne Decision-Making Questionary" developed by Mann and Ark. (1998) and Personal Information Form consisting of 7 questions. The data were evaluated by SPSS package statistical software and the significance level was taken as p<0.05. Finally; while examining the self-respect and decision-making styles in decision-making of individuals participating in the Training of Camp Learship in terms of "gender, age and education level"; it was observed that difference between score averages of sub-dimensions of decision-making styles in terms of age variables is in the sub-dimension of "suspensive decision-making style", and that also no difference in the gender and education level was observed. Consequently, it was found that as age grows, they have more suspensive decisionmaking style.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Decision-making; Self-respect; Camp; Leadership; Camp training center